Analisis Laba atas Ekuitas dan Inflasi terhadap Stock Price - Efriyenty, Dian (E-Jurnal Akuntansi, 2021)
The phenomenon of several companies experiencing stock price fluctuations can affect inflation and return on equity. The research objective is to implement the analysis of return on equity and inflation in stock prices. The population in the survey was 49 consumer goods industries in 2015-2019. Samples were carried out by purposive sampling for 10 business units. Research data analyzers with the help of self-testing and concurrent testing. The joint test results show the impact of return on equity, inflation is not significant. Meanwhile, the return on equity and inflation simultaneously have an impact on share prices. Keywords: Return On Equity; Inflation; Stock Price.